1977
DOI: 10.1111/j.1471-0307.1977.tb01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Whey by Means of Membranes and Some Applications of Whey Protein Concentrate

Abstract: Data are given for processing Gouda cheese whey by reverse osmosis as preconcentration before transport or evaporation or ultrafiltration. Concentration costs for reverse osmosis are less than those for evaporation at ×2 concentration. Data are given for processing Gouda whey by ultrafiltration. Means to reduce oxidation defects in dried whey protein concentrate during storage are discussed. Applications of whey protein concentrate in soft drinks and in flour confectionery are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 6 publications
0
5
0
3
Order By: Relevance
“…For example, it has been found that the presence of fat impairs the whipping properties of whey protein concentrate (WPC) (McDonough et al 1974, De Wit 1984. Lipids are also susceptible to oxidation and thus contribute to an off-flavour, which is best prevented by the removal of lipids from the whey (De Boer et al 1977). Removal of the residual lipids also increases ultrafiltrationpermeation fluxes (Lee and Merson 1976, Merin et al 1983, Maubois et al 1987).…”
Section: Lipoproteinsmentioning
confidence: 99%
“…For example, it has been found that the presence of fat impairs the whipping properties of whey protein concentrate (WPC) (McDonough et al 1974, De Wit 1984. Lipids are also susceptible to oxidation and thus contribute to an off-flavour, which is best prevented by the removal of lipids from the whey (De Boer et al 1977). Removal of the residual lipids also increases ultrafiltrationpermeation fluxes (Lee and Merson 1976, Merin et al 1983, Maubois et al 1987).…”
Section: Lipoproteinsmentioning
confidence: 99%
“…En revanche, au chapitre des inconvénients, il faut citer la concentration des contaminants, qui est à éviter dans le cas de concentrés protéiques destinés aux laits maternisés. La concentration des lipides résiduels ainsi que la concentration de certains métaux catalysant les réac-tions d'oxydation (fer, cuivre) associés aux protéines peut provoquer l'apparition de saveurs indésirables (De Boer et al, 1977). De plus, la présence de lipides résiduels affecte les propriétés fonctionnelles et peut expliquer que les résultats de certains travaux concernant la substitution des CPL au blanc d'oeuf soient contradictoires (De Wit et De Boer, 1975b;.…”
Section: Concentrés Obtenus Par Ultrafiltrationunclassified
“…La matière grasse accélèrerait l'effondrement de la mousse obtenue avec les protéines laitières (Edwards, 1984). De Boer et al (1977) ont montré que l'élimination des lipides résiduels confère aux CPL les mêmes propriétés moussantes que le blanc d'oeuf. La clarification des lipides rési-duels semble la meilleure méthode pour éliminer les défauts de saveur des CPL au cours de la conservation et maintenir les propriétés fonctionnelles (De Wit, 1981).…”
Section: Concentrés Obtenus Par Ultrafiltrationunclassified
See 1 more Smart Citation
“…McDonough et al (1974) and de Wit (1984) showed that the presence of fat impairs the whipping properties of a whey protein concentrate (WPC). Lipids are also susceptible to oxidation and thus may contribute to an off-flavour, which is best prevented by removal of lipids from whey (de Boer et al 1977). In a clarification method introduced by Maubois et al (1987) for the pretreatment method of whey, the residual fat and lipid components were removed with microfiltration.…”
mentioning
confidence: 99%